A Study of Pain Threshold, Interleukins and NLR in Diabetic Polyneuropathy in a Selected Nigerian Population (Nigerian Journal of Physiological Sciences, 2021)
Summary: Pain serves a protective function and is often lost in chronic conditions such as painful diabetic neuropathy (PDN). This has been reported to be associated with ongoing inflammation. This study aims to investigate an association between body immune responses, neutrophil-lymphocyte ratio (NLR) and pain perception in DPN patients. Sixty volunteers were recruited for the study. 30 control and 30 diagnosed DPN patients (used Biothesiometer). All subjects were trained and informed consents were obtained. The pain threshold was significantly (p